A family of estimators of population mean using multi-auxiliary variate and post-stratification - Vishwakarma, Gajendra K. K.; Singh, Housila P. P.; Singh, Sarjinder (Nonlinear Analysis: Modelling and Control, 2010)
This paper suggests a family of estimators of population mean using multiauxiliary variate based on post-stratified sampling and its properties are studied under large sample approximation. Asymptotically optimum estimator in the class is identified alongwith its approximate variance formulae. The proposed class of estimators is also compared with corresponding unstratified class of estimators based on estimated optimum value. At the end, an empirical study has been carried out to support the proposed methodology.
Keywords: multi-auxiliary variate; study variate; bias; variance; post-stratified sampling